Elaboration of curcumin-loaded rice bran albumin nanoparticles formulation with increased in vitro bioactivity and in vivo bioavailability. (April 2018) - Liu, Chun; Yang, Xiaoquan; Wu, Wei; Long, Zhao; Xiao, Huaxi; Luo, Feijun; Shen, Yingbin; Lin, Qinlu
Abstract: Curcumin, a yellow pigment present in the spice turmeric ( Curcuma longa ), has been linked with various bioactivities, but its optimum potential is limited by its lack of dispersibility in aqueous solvents and poor oral bioavailability. Here, we employed a protein-based nanoparticle approach to improve bioactivity and bioavailability. Curcumin was encapsulated with 95.94% efficiency in biodegradable nanoparticulate formulation based on rice bran albumin (RBA). The mean particle diameter and ζ -potential of curcumin-loaded RBA nanoparticles (Cur-RBA-NPs) were 120 nm and −36.3 mV, respectively. The in vitro bioactivity and in vivo bioavailability of Cur-RBA-NPs were evaluated. The results indicated that the in vitro bioactivities (antioxidant activity, anti-inflammatory activity, and anti-proliferative activity on tumor cells) of Cur-RBA-NPs were superior to those of free curcumin, respectively. Moreover, Cur-RBA-NPs significantly enhanced the bioavailability of curcumin in rats as compared with free curcumin. Besides, the results clearly indicated the promise of RBA-based nanoparticles for oral delivery of poorly bioavailable molecules like curcumin. Graphical abstract: Image Highlights: Curcumin was encapsulated with 95.94% efficiency in biodegradable nanoparticulate formulation based on rice bran albumin. The in vitro bioactivities of Cur-RBA-NPs were superior to those of free curcumin. Cur-RBA-NPs significantly enhanced the bioavailability of curcumin in rats as compared with free curcumin.